Determinants of profitability, liquidity, solvency, and activity ratios on the stock price with dividend payout as moderating variable - Sihombing, Pardomuan; Zakchona, Elia (Jurnal Ekonomi dan Bisnis, 2024)
This study aimed to examine the impact of financial performance proxied to profitability, liquidity, solvency, and activity ratio, as well as the moderating influence of dividend policy on stock price of Sharia-compliant companies in the Indonesia Stock (IDX) market. Panel data multi-linear regression with the random effect estimator was used to investigate the factors influencing the Jakarta Islamic Index (JII) stock price. The sample data was confined to complete audited financial reports and consistent dividend distribution to ensure the robustness of the findings. The cross-section data included 15 listed companies in JII indices, while the time series information spans financial reports published from 2016 to 2021 in the IDX market. The results showed that Profitability, represented by Return-On-Equity (ROE), positively impacted the company’s stock price listed in the JII index. Meanwhile, Solvency proxied by Debt-to-Equity Ratio (DER) and Activity Ratio measured through Total Assets Turnover (TATO) negatively affected the company’s stock price in the JII index. The liquidity represented by the Current Ratio (CR) and the Dividend Policy gauged by the Dividend Payout Ratio (DPR) also does not affect the company’s stock listed in the JII index. Furthermore, DPR did not moderate the effect of ROE on the company’s stock price listed in JII indices.